Vilania e homossexualidade: o personagem Félix Khoury da telenovela Amor à vida nas leituras da Comunidade LGBT na cidade de São Paulo - Cretaz, Lívia (2015)
This research aims to discuss the relation between villainy, redemption and homosexuality through the character of Félix Khoury from the soap opera Amor à vida (Rede Globo, 2013). This work took as object readings from the character under discussion by members of the LGBT (Lesbian, Gays, Bisexuals and Transgender) Community in the city of Sao Paulo. The primary objective is to understand in which dimension the relation between communication, consumption, villainy and gender issues represented on the soap opera were appropriated by the LGBT Community. In parallel, the aim is to map the representations of homoeroticism in Brazilian soap operas; identifying which readings were made based on an homosexual as villain; investigating the repercussions of the male gay kiss on the soap opera in question and, finally, identify how the homoeroticism is characterized as textual appeal. The theoretical foundation was based on the fields of Communication, Reception, Consumption, Soap opera and Queer Teory. In order to conduct the research, we adopted a qualitative methodology from conducting focus group, where selected scenes were debated with the interviewees in accordance with the deliberated profile. The empirical research enabled to identify issues such as identification of character s family conflicts by the public, like the search for family acceptance, rejection of the stereotypical characterization of homosexual characters.